WORD FAMILIARITY EFFECTS IN EFL READING: AN EYE TRACKING STUDY - Emrah Dolgunsöz (International Online Journal of Education and Teaching, 2018)
Do you know what happens in mind when we encounter a novel word while reading a newspaper, a paragraph or a short story? Via eye tracking technique, this study aimed to gather clues about how our mind reacts to an unknown word while we read in another language by examining word familiarity effects on eye movements during EFL reading. After a vocabulary test, eye movements of 60 EFL learners at intermediate level were recorded while they read identical sentence pairs including words with different length and frequency. The results showed that (1) total time spent on words and reanalysis times were predicted by vocabulary knowledge, (2) initial word processing was not predicted by vocabulary size (3) unfamiliar words attended more attention and required more cognitive effort than familiar words, (4) familiar words are processed in similar time spans for English as L1 and L2 but unfamiliar words cause more cognitive load in EFL. The results were discussed in comparison to L1 eye movement research in reading and were evaluated regarding EFL reading in terms of noticing hypothesis, incidental vocabulary acquisition and EFL reading instruction.